Indonesia - Stads, Gert-Jan; Surahman, Arif; Omot, Norah; Nin-Pratt, Alejandro; Nguyen, Pham Thi (International Food Policy Research Institute, 2020)
Indonesian agricultural R&D spending declined steadily in the decade leading to 2017 (in inflation-adjusted terms). The country’s agricultural research spending as a share of AgGDP also fell substantially, from 0.48 percent in 2004 to just 0.17 percent in 2017. This ratio is among the lowest in Southeast Asia.